Proposed Designs for Elderly Physical Body Problems - Al-Omari, Samira Saad; Al Dabbagh , Maha Abdullah (Advances in Social Sciences Research Journal, 2022)
The issues and needs of the elderly are receiving attention in various countries of the world. Scientific studies in the field of elderly care have confirmed that old age is a normal developmental stage of growth, which requires the need to work on developing plans aimed at integrating the elderly into society to benefit from their efforts and experiences because they are an essential part of society as well as studying the difficulties they face. Therefore, this study sought to identify the best specifications of smart and functional clothing for the elderly. It also aimed to find out the specifications of smart textiles suitable for the elderly and the requirements for the appropriate functional design for the elderly, according to their needs and desires. It also investigated the possibility to combine smart textiles with functional clothing to set specifications for smart and functional clothing for the elderly. This study was based on the descriptive and applied approaches. The study has managed to propose 5 solutions for 5 elderly body physical problems. The study recommended that clothing factories should be informed of the functional clothing specifications for the elderly, and to draft a measurement table for the elderly, and developing smart textile technologies to serve the elderly.